Chemical Composition and Biological Activity of Ferula aucheri Essential Oil - Sheyda Ahmadi koulaei; Abbas Hadjiakhoondi; Mohammad Reza Delnavazi; Zahra Tofighi; Yousef Ajani; Fatemeh Kiashi; Narguess Yasa* (Iranian Society of Pharmacognosy, 2020)
Background and objectives: Antibiotics resistance and unpleasant side effects of AChE inhibitors have led to an increased interest in herbs as potential sources. Ferula aucheri (Syn: Dorema aucheri) an indigenous species of Ferula (Apiaceae) grows in Iran and is used as food and medicinal plant. The present study was aimed to identify the oil composition and evaluate antimicrobial and AChE inhibitory activity of flowering tops, fruits and roots. Methods: The chemical composition of the oils was recognized by GC and GC‐MS. The antimicrobial effects were assessed on 12 microorganisms by disc diffusion and micro-well dilution methods and AChE inhibitory potentials by a modified version of Ellman's method. Results: Sixty five compounds were identified from different organs and the notable characteristics have been high amounts of sesquiterpenes. Germacrene B (14.96%) and β-caryophyllene (12.87%) were distinguished as major components of flowering tops. Cis-dihydroagarofuran (9.02%) and δ-cadinene (8.28%) were identified as the remarkable constituents of fruit. δ-cadinene (18.25%) and gurjunene (12.62%) were detected from the roots by high content. All volatile oils exhibited lower MICs on Bacillus subtilis, Klebsiella pneumonia, Shigella dysenteriae,and Salmonella paratyphi-A serotype compared with gentamicin. Root and fruit oils were more effective than gentamicin against Escherichia coli and flowering tops oils proved lower MICs versus Staphylococcus aureus. Fruits and root oils showed weak potency for inhibiting AChE with IC50 values 554.05±4.65 and 239.69±3.5 μg/mL, respectively and flowering tops exhibited moderate activity (179.06±4.3 μg/mL). Conclusion: The findings demonstrated that F. aucheri essential oils possessed antimicrobial activities with inhibition properties toward AchE.